ANALISIS STABILITAS PENGARUH SBI, INFLASI, DAN KURS TERHADAP INTERMEDIASI BANK UMUM DI INDONESIA PASCA KENAIKAN HARGA BBM 2010 - Chusunul Intan Cintyawardani (Jurnal Ilmiah Mahasiswa FEB, 2015)
This research aims to show the stability analysis of influence of SBI Rate, Inflation, and Exchange Rate against a common bank intermediation in Indonesia after the increase price of fuel in October 2010. The author  uses intermediation as the dependent variable and include SBI rate, inflation, and exchange rate as an independent variable. The author uses quantitative research methods and using multiple linear reggression and chow test with time series data. The results showed to determine whether the effect of the SBI, inflation and unstable exchange rate on commercial bank intermediation in Indonesia after the increase in fuel prices in October 2010. Independent variables are significant to influence intermediation. And stability influence to intermediation. Kata kunci: Intermediation, SBI rate, Inflation, Exchange rate, multiple linear regression, chow test.